Better retention of Malaysian opiate dependents treated with high dose methadone in methadone maintenance therapy - Talib Nazila; Musa Nurfadhlina; Bakar Nor; Mohamad Nasir; Ismail Rusli (BMC, 2010)
Abstract Background Methadone is a synthetic opiate mu receptor agonist that is widely used to substitute for illicit opiates in the management of opiate dependence. It helps prevent opiate users from injecting and sharing needles which are vehicles for the spread of HIV and other blood borne viruses. This study has the objective of determining the utility of daily methadone dose to predict retention rates and re-injecting behaviour among opiate dependents. Methods Subjects comprised opiate dependent individuals who met study criteria. They took methadone based on the Malaysian guidelines and were monitored according to the study protocols. At six months, data was collected for analyses. The sensitivity and specificity daily methadone doses to predict retention rates and re-injecting behaviour were evaluated. Results Sixty-four patients volunteered to participate but only 35 (54.69%) remained active and 29 (45.31%) were inactive at 6 months of treatment. Higher doses were significantly correlated with retention rate (p < 0.0001) and re-injecting behaviour (p < 0.001). Of those retained, 80.0% were on 80 mg or more methadone per day doses with 20.0% on receiving 40 mg -79 mg. Conclusions We concluded that a daily dose of at least 40 mg was required to retain patients in treatment and to prevent re-injecting behaviour. A dose of at least 80 mg per day was associated with best results.